Building communism: the Young Communist League during the Soviet thaw period, 1953-1964 - Uhl, K; Katharina Uhl (2014)
The present study focuses on the activity of the Young Communist League (Komsomol) to promote the communist project during the so-called Thaw period in the Soviet Union (1953-1964). The term ‘communist project’ describes the complex temporal triangle in which the relevance of the present was rooted in its relationship to the heroic past and the bright future. Young people were supposed to emulate the heroism of previous generations while fighting remnants of the undesired past. This was presented as a precondition for achieving the communist future. The structure of this study reflects the chronology of the communist project. It analyzes the rhetoric used by the Young Communist League to promote the communist project and explores the strategies used to mobilize youth for building communism. The first chapter focuses on the organizational structure of the Komsomol and assesses its readiness for this task. Despite attempts to strengthen horizontal communication and control, streamline administration and reorganize its structure, the Komsomol remained hierarchal and bureaucratic. The second chapter explores the promotion of past heroism in rituals, social practices and the use of public space. The third chapter is also concerned with the past; it describes the Komsomol’s fight against ‘remnants of the past’, primarily religion and deviant behaviour such as hooliganism, heavy drinking and laziness. The final chapter focuses on the Komsomol’s attempts during the Thaw to bring about the future: its efforts in the economy, moral, political and cultural education, and the realm of leisure.